Analysis of the Fine Structure of the D‐Exciton Shell in Cuprous Oxide. Issue 11 (4th October 2021) - Heckötter, Julian; Rommel, Patric; Main, Jörg; Aßmann, Marc; Bayer, Manfred
Abstract : The exciton states in cuprous oxide show a pronounced fine structure splitting associated with the crystal environment and the resulting electronic band structure. High‐resolution spectroscopy reveals an especially pronounced splitting of the yellow D excitons with one state pushed above any other state with the same principal quantum number. This large splitting offset is related to a strong mixing of these D states with the 1 S exciton of the green series, as suggested by previously published calculations. Here, a detailed comparison of this theory with experimental data is given, which leads to a complete reassignment of the experimentally observed D exciton lines. The origin of different amounts of green admixture to D ‐envelope states is deduced by analyzing the different terms of the Hamiltonian. The yellow–green mixing leads to level repulsion and induces an exchange interaction splitting to D ‐envelope states, from which one of them becomes the highest state within each multiplet. Furthermore, the assignment of D exciton states according to their total angular momentum F is given and corrects an earlier description given in a former study. Abstract : The fine structure of yellow D ‐envelope excitons in bulk Cu2 O is analyzed. A large splitting of these states is observed in experiment. A detailed theoretical analysis relates the splitting to a mixing with the green exciton series. Due to this mixing, one of the D excitons is shifted energetically above the F ‐envelope excitons.